Design of Upper Limb Active Rehabilitation System Based on Somatosensory Interaction Technology and Reliability and Validation Analysis - MAI Wangxiang; ZHENG Jiaxing; HE Weiyi; FANG Liang; SHANG Yaru; LI Wanyue; CHEN Zhuoming (康复学报)
ObjectiveTo develop an upper limb active rehabilitation system with Kinect somatosensory interaction technology based on the basic rehabilitation theory and different stages of rehabilitation treatment for the post stroke hemiplegic patients to improve the effect of rehabilitation treatment.MethodsVirtual training scenarios were created with 3D modeling technology, and the human body posture and movements were detected with the Kinect somatosensory interaction technology. Based on the plasticity of the central nervous system, Brunnstrom theory, motor re-learning, and other rehabilitation theories, this study designed the virtual games in line with the characteristics of upper limb motor dysfunction after stroke. Meanwhile, the real-time feedback was given to the training of patients. Finally the upper limb exercise rehabilitation training system was established, and the validity and reliability of the rehabilitation system for the measurement of upper limb joint range of motion were verified. An upper limb active rehabilitation system was designed using the Kinect somatosensory interaction technology.ResultsThe system included several virtual trai-ning games such as cutting food and shooting. Through motion detection and discrimination algorithm, the system realized the interaction between patients and virtual environment, as well as the evaluation of motor function and real-time feedback of joint range of motion information. The measurement of shoulder abduction, flexion, extension, elbow flexion and other joint range of motion in the system had a high consistency with the set target values. The Bland-Altman was used for comparison. The 95% consistency limits of shoulder abduction range of motion in the system was (-1.29, 1.57). The 95% consistency limits for shoulder flexion range of motion was (-1.46, 1.60), the 95% consistency limits for shoulder extension range of motion was (-1.53, 1.67), and the 95% consistency limits for elbow flexion range of motion was (-1.42, 1.56), indicating good system validity. Intra-group correlation coefficient (ICC) was used to evaluate the reliability of the system. In test-retest reliability, the ICC of shoulder abduction, flexion, extension and elbow flexion were all greater than 0.9. In terms of interobserver reliability, the ICC of all four joint range of motion were greater than 0.9.ConclusionThis upper limb active rehabilitation system designed based on somatosensory interaction technology has good validity and reliability, strong feasibility, which can meet the needs of clinical upper limb rehabilitation, and provide a new method for the rehabilitation of upper limb function after stroke. Compared with the traditional upper limb training, it is highly targeted and interesting, and is expected to improve the efficiency of rehabilitation treatment.